2007
DOI: 10.2174/138920007780655432
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Cytotoxic Activity of Recombinant TRAIL Plus the Non-Genotoxic Activator of the p53 Pathway Nutlin-3 in Acute Myeloid Leukemia Cells

Abstract: To potentiate the response of acute myeloid leukemia (AML) to TRAIL cytotoxicity, we have adopted a strategy of combining nutlin-3, a potent non-genotoxic activator of the p53 pathway, with recombinant TRAIL. The rationale for using such a combination was that deletions and/or mutations of the p53 gene occur in only 5-10% of AML and that TRAIL and nutlin-3 activate the extrinsic and intrinsic pathways of apoptosis, respectively. TRAIL induced a rapid increase of apoptosis when added to OCI M4-type and MOLM M5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 0 publications
2
45
1
Order By: Relevance
“…33,46 Our data provide evidence that such therapeutic strategies can be improved by incorporation of agents such as nutlin-3a, in agreement with others. 47,48 Recent studies have shown that nutlin-3a, at very high concentrations, usually 420-30 mM, can inhibit the growth of cancer cells with deleted p53, or harbouring a nonfunctional, mt p53 gene, although the exact mechanism is incompletely understood. 35,36 It seems, depending on the in vitro system, that activation of other partners of Mdm2, including p73 or E2F1, may be involved in this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…33,46 Our data provide evidence that such therapeutic strategies can be improved by incorporation of agents such as nutlin-3a, in agreement with others. 47,48 Recent studies have shown that nutlin-3a, at very high concentrations, usually 420-30 mM, can inhibit the growth of cancer cells with deleted p53, or harbouring a nonfunctional, mt p53 gene, although the exact mechanism is incompletely understood. 35,36 It seems, depending on the in vitro system, that activation of other partners of Mdm2, including p73 or E2F1, may be involved in this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…wild-type (p53 wt ) status (3)(4)(5)(6)(7)(8)(9). However, because p53 mediates different cellular functions, such as in particular cell-cycle arrest and apoptosis (3) the critical molecular determinants mediating/modulating the therapeutic activity of Nutlin-3 in leukemic cells are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, unlike solid tumors, mutations and/or deletions of p53 in hematologic malignancies have been detected in less than 20% of patients at diagnosis, mostly in patients with 17p monosomy, which is often associated with TP53 mutation of the second allele (12). Of note, recent studies have shown that Nutlin-3, used alone or in combination with chemotherapeutic drugs, effectively increases the degree of apoptosis in different hematopoietic malignancies (13)(14)(15), including B-CLL (16)(17)(18)(19). In spite of these studies, the potential mechanisms of action of Nutlin-3 are still not completely understood.…”
Section: Introductionmentioning
confidence: 99%